2009
DOI: 10.1007/s11250-009-9450-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological change in camel milk composition (Camelus dromedarius) 2: physico-chemical composition of colostrum

Abstract: Eleven samples of dromedary camel colostrum in Kazakhstan, which originated from one farm only, were collected to study the changes in the physico-chemical composition (total fat, total protein, iodine index, lactose, calcium, phosphorus, iron, vitamin C, urea, ammonia, density, Dornic acidity, pH, and skimmed dry matter) all along the first postpartum week. At that time, the fat matter decreased from 25.9% to 3.1% and protein from 17.2% to 4.2%, in contrast to vitamin C which increased. Minerals showed high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Although one could have expected somewhat lower lipid content for spring samples because of potentially lower food intake during winter season, those data do not describe a clear seasonal influence on the lipid content for both species. Globally, the reported mean values are similar to the few available values for Kazakhstan, as reported by Konuspayeva et al (2010) 5.9 ± 2.5%, Serikbaeva and Toktamysova, 2000 5.2%, and Urbisinov (unpublished results) 5.1%.…”
Section: Lipid Contentssupporting
confidence: 88%
“…Although one could have expected somewhat lower lipid content for spring samples because of potentially lower food intake during winter season, those data do not describe a clear seasonal influence on the lipid content for both species. Globally, the reported mean values are similar to the few available values for Kazakhstan, as reported by Konuspayeva et al (2010) 5.9 ± 2.5%, Serikbaeva and Toktamysova, 2000 5.2%, and Urbisinov (unpublished results) 5.1%.…”
Section: Lipid Contentssupporting
confidence: 88%
“…Konuspayeva et al (2010) found that TP decreased from 17.2 to 4.2% in 7 days. The high content of TP in during the colostrum secretion can be explained by the high content of immunoglobulins in mammary secretion at this stage.…”
Section: Colostrum and Early Lactationmentioning
confidence: 92%
“…In 2009, El-Agamy reported the amount of iron in camel milk as 0.7-3.7 mg/L (El-Agamy, 2009). In study by Konuspayeva et al (2010), the mean amount of iron in camel colostrum was measured by ICP method resulting in the amount of 2.50 mg/L. Al Haj & Al Kanhal (2010) and Nnadozie et al (2014) reported the mean iron content in camel milk as 0.29 mg/100 g and 0.146 mg/kg, respectively.…”
Section: Mineral Contentsmentioning
confidence: 99%